How bright is moonlight?. Issue 1 (1st February 2017) - Kyba, Christopher C M; Mohar, Andrej; Posch, Thomas
Abstract : Christopher Kyba, Andrej Mohar and Thomas Posch seek a standard figure for moonlight illuminance. Abstract : Christopher Kyba, Andrej Mohar and Thomas Posch seek a standard figure for moonlight illuminance.